2019
DOI: 10.1111/mec.15228
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted aspects of synchrony between freshwater prokaryotes and protists

Abstract: Community composition of freshwater prokaryotes and protists varies through time. Few studies contemporarily investigate temporal variation of these freshwater communities for more than 1 year. We compared the temporal patterns of prokaryotes and protists in three distinct habitats for 4 years (2014–2017) in Lake Tovel, a cold‐water lake. This lake showed a marked temperature increase in 2017 linked to altered precipitation patterns. We investigated whether microbial communities reflected this change across ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…We attributed this year effect to a change in the lake’s hydrology. The years from 2014 to 2017 showed a decreasing gradient in precipitation (Obertegger et al, 2019). Furthermore during the year 2017, Lake Tovel experienced a shift from nival to pluvial origin of its waters, leading to whole lake warming and increased stability of the water column (Flaim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We attributed this year effect to a change in the lake’s hydrology. The years from 2014 to 2017 showed a decreasing gradient in precipitation (Obertegger et al, 2019). Furthermore during the year 2017, Lake Tovel experienced a shift from nival to pluvial origin of its waters, leading to whole lake warming and increased stability of the water column (Flaim et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature values taken with a multiparametric probe (Idronaut Ocean Seven 316 Plus) at 1‐m intervals were averaged within the respective profile for the littoral (0–4 m), pelagic (0–20 m), and deep hypolimnion (30–35 m). Precipitation (mm), provided from the onshore meteorological station, and water level change (cm) were averaged for the 10 days before sampling as in Obertegger et al (2019). Total yearly precipitation (mm) at Lake Tovel showed a decreasing gradient from 2014 to 2017 (2014: 1867 mm; 2015: 1027 mm; 2016: 1110 mm; 2017: 978 mm; Obertegger et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoplankton and heterotrophic bacteria are linked in multiple ways such as competition for nutrients, use of algal exudates, decomposition of decaying algae, or mixotrophic predation of algae on bacteria (Bižić-Ionescu et al, 2014;Salcher, 2014;Unrein et al, 2014;Ivanova et al, 2018). While prokaryotes and protists are in temporal synchrony in Lake Tovel during the ice-free period (Obertegger et al, 2019), this study indicated temporal differences. Small environmental differences in under-ice conditions can have huge impacts on phytoplankton composition (Vehmaa & Salonen, 2009), and we suggest that year-to-year variability in under-ice environmental conditions and biotic interactions (e.g.…”
Section: Discussionmentioning
confidence: 59%
“…However, longer term studies eventually reflecting seasonal patterns are still very rare (Gilbert et al, 2012; Karl & Church, 2014; Linz et al, 2017). Furthermore, most microbial diversity studies, including temporal surveys, focus on either archaeal, bacterial or eukaryotic communities, but an integrated view of how the two change with time, eventually revealing underlying biotic interactions, are extremely scarce and restricted to large environments such as oceans and lakes (Biller et al, 2018; Obertegger et al, 2019; Steele et al, 2011). Yet, differences in overall metabolic capabilities, physiology, trophic features, generation time and dispersal might be reflected in distinct temporal patterns of bacteria and archaea vs. microbial eukaryotes.…”
Section: Introductionmentioning
confidence: 99%